Unlocking the potential of water-soluble gold( i )–NHC complexes: unveiling the role of carboxylic acid in cycloisomerization of alkynyl amino acid derivatives - Pérez Hincapié, Liddier Oiden (2024)
Hydrocarboxylationof alkyne-containing amino acid derivatives using water-soluble gold(I)–NHCcomplexes in an aqueous biphasic system at room temperature is described.Addition of silver salts is not required as the carboxylic acid group of thesubstrate is responsible for the activation of the gold catalyst at roomtemperature. Our result confirms that the steric bulk of the N-heterocyclic carbene ligands is animportant factor in both the stability and the catalytic activity of gold(I)complexes in aqueous medium, and consequently in the recycling (at least 15times without any loss of activity). The catalytic activity of our most activewater-soluble gold(I)–NHC complex has been demonstrated in thecycloisomerization of amino acids derivatives with terminal and internal alkynesin aqueous media at room temperature.